LOCAL POLITICS ARISTOCRACY OF BALI IN THE POST-REFORM ERA - I Gusti Ayu Agung Dewi Sucitawathi Pinatih; Kacung Marijan; I.B. Wirawan (Universitas Padjadjaran, 2022)
Puri (Balinese palace) is one of the cultural symbols of the Balinese people. The power system that once placed puri as a central actor became a political tradition that led to the local politics aristocracy model which still adopted the values of feudalism, including in the political life of government. This study itself aims to analyze the political culture that shapes the pattern of local politics aristocracy of Bali in the post-reform era. The theories used to analyze the problem are elite theory and patron-client theory using the point of view of political sociology. The research method is qualitative research in the form of literature studies derived from books, journals, and descriptive analysis related to the research topic. The findings in this study are that the survival of puri in Bali is caused by an elitist political culture that is influenced by the caste system, and the position of the puri which places itself as a patron (ruler) to clients (community) related to religion, economy, and politics.